1ISG-006 Contamination of the blister packs by pomalidomide after use in clinical situation. (2nd March 2018) - Iwaki, T; Takahashi, Y; Kaneta, A; Yashima, H; Abe, T; Araki, T; Yamamoto, K
Abstract : Background: Blister pack is commonly used as a package of internal medicine in Japan. In addition, emptied blister packs of particular drugs are recovered by pharmacists to check their appropriate use. Pomalidomide is an orally active thalidomide analogue and used for multiple myeloma. Because it has both high efficacy and risk of teratogenicity, the use of Pomalyst capsules is strictly managed through the RevMate procedure. Pharmacists must recover emptied blister packs of Pomalyst capsules from all patients according to guidance from the Celgene Corporation. However, the risk of exposure of pomalidomide via the used blister packs to pharmacists have not been well assessed. Purpose: To prevent pharmacists from unintended exposure to pomalidomide, the contamination level of pomalidomide on the surface of used blister packs in the normal clinical situation was assessed. Material and methods: The used blister packs of Pomalyst capsules, seven-tablet PTP sheets, were recovered from five patients. Pomalidomide was extracted and its amount was analysed by LC-MS/MS. Separation was performed on an ACQUITY UPLC BEH C18 column (Waters, 1.7 µm, 2.1 mm ×50 mm). The mobile phase consisted of a mixture of phase A (0.1% formic acid in water) and phase B (acetonitrile). Transition channel of the protonated molecular ions was 274.17/201. 12 were used for detection of pomalidomide. Results: The amount of pomalidomide was 2.33±4. 60 µg per blister pack (0.1–10 µg per blister pack). Conclusion: In this study, although most used blister packs were contaminated by pomalidomide at a very low level, a sheet was contaminated at a high level of approximately 10 µg of pomalidomide. Because pomalidomide is known for high teratogenicity, our data suggested that the standard protection procedure was recommended to prevent unintended exposure to the drug for pharmacists. No conflict of interest